A new design of pulsed laser diode driver system for multistate quantum key distribution - Abdullah M.S.; Jamaludin M.Z.; Witjaksono G.; Mokhtar M.H.H. (2023)
In this paper, we describe a new design of laser diode driver system based on MOSFET current mirror and digital signal controller (DSC). The system is designed to emit stream pairs of photons from three semiconductor laser diodes. The DSC is able to switch between the three laser diodes at constant rate. The duty cycle is maintained at 1% in order to reduce its thermal effect and thus prolong the laser diodes' life cycles. The MOSFET current mirror circuits are capable of delivering constant modulation current with peak current up to 58 mA to each laser diode. This laser driver system will allow the generating biphotons automatically with qubit rate around 813% for ? less than or equal to 1, thus making it practical for six-states quantum key distribution implementation. 2010 Elsevier Ltd. All rights reserved.